2019
DOI: 10.1038/s41598-019-44233-z
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic and shear-thinning effects of aqueous exopolymer solution on disk and sphere settling

Abstract: In this study, xanthan gum is used as a model exopolymer to demonstrate potential effects of non-Newtonian properties of natural aquatic systems on settling dynamics of particles. Rheological measurements combined with settling experiments using visualization methods revealed that instantaneous velocity fluctuations and a flow pattern formed around a particle are the effects of solution viscoelasticity and shear-thinning properties and that the average settling velocity depends on the exopolymer concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 57 publications
(124 reference statements)
1
14
1
Order By: Relevance
“…Polymer melts and aqueous solutions also exhibit a non-Newtonian behavior. Those mixtures mostly display shear thinning, but, even if less common, a shear thickening effect can be encountered. , Bokias et al reported that in most cases, shear thickening is not very pronounced and appears only at rather low shear rates. As a general trend, the overall rheological behavior of polymer aqueous solutions is driven by both the polymer concentration and microstructure, , since they determine the nature and the ability of forming inter- and intrachain junctions (usually reversible) for polymer macromolecules in aqueous media. , In such a way, flexible-backbone (block) copolymers with amphiphilic properties were synthesized over the past decades to have water-soluble entities. , Usually, water-soluble polymers are modified to contain a small number of hydrophobic groups .…”
Section: Introductionmentioning
confidence: 99%
“…Polymer melts and aqueous solutions also exhibit a non-Newtonian behavior. Those mixtures mostly display shear thinning, but, even if less common, a shear thickening effect can be encountered. , Bokias et al reported that in most cases, shear thickening is not very pronounced and appears only at rather low shear rates. As a general trend, the overall rheological behavior of polymer aqueous solutions is driven by both the polymer concentration and microstructure, , since they determine the nature and the ability of forming inter- and intrachain junctions (usually reversible) for polymer macromolecules in aqueous media. , In such a way, flexible-backbone (block) copolymers with amphiphilic properties were synthesized over the past decades to have water-soluble entities. , Usually, water-soluble polymers are modified to contain a small number of hydrophobic groups .…”
Section: Introductionmentioning
confidence: 99%
“…Image pre-processing, processing and analysis were carried out using ImageJ and MATLAB® as in the previous studies 25 , 51 . In each raw grayscale image, a particle was detected using thresholding.…”
Section: Methodsmentioning
confidence: 99%
“…A negative wake has also been observed for solid spheres settling in viscoelastic fluids [51][52][53]. A large amount of research has been done on the "negative wake" of solid balls and discs compared with the experimental research done for bubbles, owing to the instability of the bubble surface [51,54,55]. ese studies show that the so-called "negative wake" could be observed in the wake of solid spheres over a wide range of Deborah numbers.…”
Section: The Negative Wake Phenomenonmentioning
confidence: 96%